Behavioral Sensitivity of Temporally Modulated Striatal Neurons - Portugal, George; Wilson, Arlington G.; Matell, Matthew S. (Frontiers in Integrative Neuroscience, 2011)
Recent investigations into the neural mechanisms that underlie temporal perception have revealed that the striatum is an important contributor to interval timing processes, and electrophysiological recording studies have shown that the firing rates of striatal neurons are modulated by the time in a trial at which an operant response is made. However, it remains unclear whether striatal firing rate modulations are related to the passage of time alone (i.e., whether temporal information is represented in an “abstract” manner independent of other attributes of biological importance), or whether this temporal information is embedded within striatal activity related to co-occurring contextual information, such as motor behaviors. This study evaluated these two hypotheses by recording from striatal neurons while rats performed a temporal production task. Rats were trained to respond at different nosepoke apertures for food reward under two simultaneously active reinforcement schedules: a variable-interval (VI-15 sec) schedule and a fixed-interval (FI-15 sec) schedule of reinforcement. Responding during a trial occurred in a sequential manner composing 3 phases; VI responding, FI responding, VI responding. The vast majority of task-sensitive striatal neurons (95%) varied their firing rates associated with equivalent behaviors (e.g., periods in which their snout was held within the nosepoke) across these behavioral phases, and 96% of cells varied their firing rates for the same behavior within a phase, thereby demonstrating their sensitivity to time. However, in a direct test of the abstract timing hypothesis, 91% of temporally modulated “hold” cells were further modulated by the overt motor behaviors associated with transitioning between nosepokes. As such, these data are inconsistent with the striatum representing time in an “abstract’ manner, but support the hypothesis that temporal information is embedded within contextual and motor functions of the striatum.